Synthesis, characterization, antimicrobial, and pharmacological evaluation of some 2, 5-disubstituted sulfonyl amino 1,3,4-oxadiazole and 2-amino-disubstituted 1,3,4-thiadiazole derivatives - Dilipkumar Pal; Rohit Tripathi; Desh Deepak Pandey; Preety Mishra (Wolters Kluwer Medknow Publications, 2014)
The presence of heterocyclic structures in diverse types of compounds, this is strongly indicative of the profound effect like structure exerts on physiologic activity, and recognition of this is abundantly reflected in efforts to find useful synthetic drugs. The search for better pharmacological active drug and the importance of disubstituted 1,3,4-oxadiazole and 1,3,4-thiadiazole as active pharmacophores, prompted us to design, synthesize, characterize, and evaluate a series of differently substituted sulfonyl amino 1,3,4-oxadiazole and 1,3,4-thiadiazole for their potential antimicrobial, analgesic and antiinflammatory activity, respectively. New sulfonyl amino 1,3,4-oxadiazole and 1,3,4-thiadiazole derivatives were synthesized by intramolecular cyclization of thiosemicarbazide in alkaline medium. Reactions were carried out by the reaction between aromatic carbonyl halide and thiosemicarbazide.